العلاقة بين حفظ القرآن الكريم لدى الطالبات للصف الثاني من المتوسطة وقدرتهن على استيعاب المفردات العربية بمعهد عبد الله بن مسعود آساهن - Annisa, Ridha; Rozaanah, Rozaanah; Jamaluddin, Muhajirah Binti (Lembaga Yasin AlSys, 2024)
What is meant by vocabulary comprehension is a person's ability to use the vocabulary he possesses to communicate and express ideas with the listener, whether in writing or orally. This ability appears when developing linguistic skills such as speaking skill, listening skill, writing skill, and reading good Arabic. The meaning of memorizing the Qur’an is the attempt to enter the verses of the Qur’an into the chest and preserve it from loss and forgetfulness and to try to read it without fault, that is, without looking at the Holy Qur’an, ensuring it, preparing it, and being upright in it. Preserving what has been memorized, protecting it from loss, preventing it from forgetfulness, mental loss, and loss, and being present must have knowledge of Arabic. From it is impossible for someone who meditates on the Holy Qur’an without knowledge of the Arabic language. Research question: Is there a relationship between memorizing the Holy Qur’an among female students in the second grade of middle school and their ability to comprehend vocabulary at the Abdullah bin Masoud Asahi Institute? What was its strength and direction? The aim of writing this research is to find out the relationship between memorizing the Holy Qur’an among female students in the second year of school. Intermediate level and his ability to comprehend vocabulary at the Abdullah bin Masoud Asahi Institute. The method used in this research is the quantitative relational method and the research method used is the statistical method with a program and the result of this research is that there is a moderate relationship between memorizing the Holy Qur’an among female students in the second year of middle school and their ability to comprehend vocabulary at the Abdullah bin Masoud Asahi Institute. The value of the coefficient. The correlation is 0,476 and its direction is the same.